JENIS IKAN KERAPU (SERRANIDAE) DAN HUBUNGAN PANJANG BERAT DIPERAIRAN BERAU, KALIMANTAN TIMUR [Grouper species and length-weight relationship in Berau waters, East kalimantan] - Siti Nuraini (Masyarakat Iktiologi Indonesia (Indonesian Ichthyological Society), 2007)
Grouper fish was identified in Berau waters in April and July 2005, and March 2006. The number of fish found was 25 species in five genera: Epinephelus, Plectropomus, Cephalopolis, Variola, and Cromileptes. Some species such as Cromileptes altivelis, Epinephelus lanceolatus, and P. aerolalus were vulnerable species; whereas Cromileptes altivelis, Epinephelus lanceolatus, P. leopardus, P. laevis dan P. aerolatus has listed in red data book. E. coioides, P. leopardus, P. laevis are isometric, and P. oligocanthus, P. laevis, V. louti are allometric.